Interpersonal violence against athletes - Schmidt, R. E.; Schneeberger, A. R.; Claussen, M. C. (Sports Psychiatry, 2022)
Abstract. The mediatization of several high-profile cases of sexual abuse in sports has sensitized a larger public for the problem of interpersonal violence against athletes. This article provides an overview of what is already known on the prevalence of different forms of interpersonal violence in sports, associated personal, organizational and cultural risk factors, and the psychopathological consequences of interpersonal violence. Throughout the article, areas where more research is needed are highlighted. It is concluded that evidence-based psychiatric and psychotherapeutic prevention, intervention and care programs that are tailored to the specific needs of athletes are needed to safeguard mental health in sports.